Public spending and informal economy in the Asian countries - Nguyen Phuc Van; Duc Hong Vo; Tran Toan Pham-Khanh; Ngoc Phu Tran (Cogent Economics & Finance, 2022)
The informal economy is a complex phenomenon present, to a large extent, in both developing and developed countries. Despite an increasing focus on the nexus between public spending and the informal economy, little is known about the moderating role of budget imbalance in this relationship. This study investigates how a budget imbalance moderates the effects of public spending on the informal economy of 32 Asian countries from 2000 to 2017. We have employed the generalized method of moments and various second-generation tests in this analysis to ensure the approach is appropriate and the findings are robust. Our results indicate that increasing public spending and budget imbalance will increase the informal economy size. Interestingly, the effect of public expenditure on the informal economy will enhance with an increase in the budget imbalance. Additionally, we also find that tax burden and economic growth contribute to the increased informal economy in Asian countries. This study also offers some useful policy implications for reducing the informal economy.
Keywords: 330; Public spending; informal economy; budget imbalance; Asian countries; GMM